Sistema Inalámbrico Modular de Bajo Costo para Supervisar Variables Ambientales en Invernaderos: Un Respaldo al Agricultor de Pequeña Escala - Monroy-García, Oscar Yesid; Rolón-Quintero, Daniel Camilo; Sepúlveda-Mora, Sergio Basilio (Revista Científica, 2017)
Farmers in Norte de Santander department supervise the microclimate in greenhouses by an intuitive estimation based on their long time experience. This method is inadequate and subjective, and it has a negative impact on the development and performance of the crops; limiting the quality and production. Therefore, this agricultural procedure requires the development and implementation of efficient technology aiming to the improvement of the production. For small-scale farmers is difficult to acquire supervision systems due to their low income and the relative high cost of this kind of technology; then, farmers prefer to prescind from the advantages of using monitoring systems in greenhouses. This paper presents the design and development of a low-cost modular system that allows the supervision of environmental variables within a greenhouse. The proposed system uses ZigBee protocol and a Wireless Sensor Network to collect data of humidity, temperature and luminosity; these variables are stored in a database and the system shows a real time plot and allows to generate reports. The Packet Reception Rate obtained in the experimental setup was between 70 % and 100 %. Besides, the proposed system has a reduction in cost of about 87 % with respect to commercial systems with similar features.